EXPLORING INDIA’S CONSTITUTIONAL COMMITMENT TOWARDS CHILDREN: THEORY AND PRACTICE - Dr. Partha Sarathi Dey (Galaxy International Interdisciplinary Research Journal, 2021)
The children are regarded as the asset of the country for its development and prosperity as they are the future citizens of nation. But in reality, they are found in most vulnerable position in maximum countries so they need to be protected. Across the world increasing attention has been paid in recent years to the notions of children rights. This paper using case study method tries to highlights the commitments of Indian Constitution relating to the protection and development of the children and to addresses the present status of children in India in respect of her commitments towards them. The study finds out that we need to go long way to fulfil the commitment made by the constitution of India. A large number of children in India is still in vulnerable position. Many children are denied basic rights, opportunities and a secure childhood as committed by our constitution. We need to urgently address these issues.